Implementation of an Education for Sustainable Development (ESD)-Based Electronic Module to Improve Critical Thinking Skills and Environmental Awareness Among Students in the Wetland Ecology Course - Wulandari, Sri; Suwondo, Suwondo; Husna, Rizqa Alfajri (FKIP - Universitas Riau, 2025)
The 21st century is known as the era of science and communication. To face these challenges, quality human resources are needed through education. This study aims to determine the improvement in critical thinking skills and environmental awareness among students after using electronic teaching materials on wetland ecology based on Education for Sustainable Development (ESD). The research used a pre-experimental design with a one-group pretest-posttest design. A total of 34 students enrolled in the wetland ecology course in the even semester of 2024/2025 participated in the study. The results showed that students' critical thinking skills improved from the pretest to the posttest. The pretest mean score was 70.47, considered good, while the posttest mean score was 84.28, considered very good. Students' cognitive environmental awareness attitudes also improved between the pretest and posttest. The students' cognitive attitude towards environmental awareness in the pretest was 3.34, considered moderately concerned, and increased to 4.3 in the posttest, considered concerned. Thus, the electronic module on wetland ecology based on ESD as teaching material enrichment can be used to improve students' critical thinking and attitude towards environmental awareness.